2020
DOI: 10.1002/adom.201902030
|View full text |Cite
|
Sign up to set email alerts
|

Lengthening the Lifetime of Common Emissive Probes to Microseconds by a Jigsaw‐Like Construction of NIR‐Responsive Nanohybrids

Abstract: Chemical/biological sensing by means of luminescence still requires improvement of signal contrast and depth of sample imaging. Though there is a considerable number of emissive molecular and quantum dot probes, most of them absorb in the UV–vis range and emit in the visible and exhibit emission lifetime in the nanoscale. Optical bioimaging in the near infrared window based on these dyes offers reduced light scattering, lower competitive absorption, and reduced background autofluorescence, but it requires a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…However, we have previously demonstrated how this drawback is, in fact, advantageous for obtaining information about the evolution of the UCNP emission over time. 30,32,46 The time-resolved NIR-LSM principle can be clearly explained by imaging an agglomerate of UC Tm @Rh110 at 4 μs per pixel dwell time. The image of Fig.…”
Section: Evaluation Of the Empirical Photoluminescence Lifetime Of Ucnps By Using Nir-lsmmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we have previously demonstrated how this drawback is, in fact, advantageous for obtaining information about the evolution of the UCNP emission over time. 30,32,46 The time-resolved NIR-LSM principle can be clearly explained by imaging an agglomerate of UC Tm @Rh110 at 4 μs per pixel dwell time. The image of Fig.…”
Section: Evaluation Of the Empirical Photoluminescence Lifetime Of Ucnps By Using Nir-lsmmentioning
confidence: 99%
“…[30][31][32] Nanohybrids can be designed to lengthen the photoluminescence of a nearby acceptor ( photoactive NPs, organic fluorophores) via resonant energy transfer (RET) from the UCNPs, which is of interest in (bio)sensing, photodynamic therapy, and bioimaging applications, and photonics. [30][31][32] Previous studies performed by our group have demonstrated that when the RET process is highly efficient, only dots (instead of tails) are observed upon 975 nm excitation of the UCNHs due to a drastic quenching of the lifetime of the UCNPs. 30 On the other hand, for moderately efficient RET, a shortening of the tail of the upconversion emission, together with a lengthening in the fluorophore lifetime, can be observed.…”
Section: Evaluation Of the Empirical Photoluminescence Lifetime Of Ucnps By Using Nir-lsmmentioning
confidence: 99%
See 3 more Smart Citations